SERVICES QUALITY AND IMAGES: SATISFACTION AND LOYALTY OF STUDENTS FACE TO FACE TUTORIAL SERVICES - Yusuf Yusuf (AFEBI Management and Business Review, 2019)
Purpose of the study is to describe service quality, image, satisfaction and loyalty, and its direct and indirect influence. Using descriptive quantitative method with the descriptive and explanatory survey. The sample is 205 students. The type of primary data used and data analysis techniques using analysis tests path. The results showed that all the average variables were high and the image variable had the highest average. Directly, service quality to satisfaction, image to satisfaction, and satisfaction with loyalty have a significant effect, satisfaction with loyalty and image of loyalty has no significant effect. Simultaneously, service quality and image of satisfaction and service quality, image, satisfaction with loyalty have a significant effect. Indirectly, satisfaction can mediate service quality towards loyalty and satisfaction capable of mediating the image of loyalty. In its implications, any increase or decrease in satisfaction indirectly will influence the loyalty of Regional Office of Open University at Pangkalpinang tutorial students.